2020
DOI: 10.1111/cen3.12610
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life and treatment strategies in myasthenia gravis

Abstract: The spread of immune treatments based on oral steroids since the 1970s has led to a non-lethal disease course and decreased severity of illness for many patients with myasthenia gravis (MG). 1-6 However, the rate of long-term complete stable remission (CSR) has not been increased and remains quite low. 1-6 Even today, many patients experience difficulties with daily activities as a result of residual fatigability and long-term side-effects of medications, such as oral steroids, and they are unable to live a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Although corticosteroids have a relatively fast onset of action, they act nonspecifically, not only in suppressing the immune system, but also in reducing bone density, and affecting the central nervous, vascular, and endocrine systems. Their long‐term use is associated with a range of adverse side effects and can negatively impact on quality of life in patients with MG 10,11,17,36–39 . Conversely, achieving minimal manifestations status or better with a prednisolone dose of ≤5 mg/d has been shown to have a significantly positive effect on health‐related quality of life in Japanese patients with MG 10 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although corticosteroids have a relatively fast onset of action, they act nonspecifically, not only in suppressing the immune system, but also in reducing bone density, and affecting the central nervous, vascular, and endocrine systems. Their long‐term use is associated with a range of adverse side effects and can negatively impact on quality of life in patients with MG 10,11,17,36–39 . Conversely, achieving minimal manifestations status or better with a prednisolone dose of ≤5 mg/d has been shown to have a significantly positive effect on health‐related quality of life in Japanese patients with MG 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Their long-term use is associated with a range of adverse side effects and can negatively impact on quality of life in patients with MG. 10,11,17,[36][37][38][39] Conversely, achieving minimal manifestations status or better with a prednisolone dose of ≤5 mg/d has been shown to have a significantly positive effect on health-related quality of life in Japanese patients with MG. 10 The current analysis demonstrated that eculizumab treatment was associated with an increase over time in the proportion of patients who were treated with a low daily oral corticosteroid dose of ≤5 mg, the current target recommended in treatment guidelines for MG in Japan. 1 This is consistent with the results of a post-hoc analysis of immunosuppressant use in the REGAIN OLE, which showed that eculizumab treatment was accompanied by significant reductions in the mean daily dose of oral prednisone and other corticosteroids-almost half of patients decreased dosage or stopped their corticosteroid during the OLE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A complement component C5 inhibitor, eculizumab, 3 and neonatal Fc receptor inhibitor, efgartigimod, 4 were recently approved for refractory cases. A few patients can achieve a complete remission with these treatments, 5 and many patients remain requiring long‐term immunotherapies. Infections are adverse effects of immunotherapy.…”
Section: Introductionmentioning
confidence: 99%